The Capacity of Legal Politics in the Job Creation Law and the Urgency of Establishing a National Central Legislative Agency: Kapabilitas Politik Hukum Undang-Undang Cipta Kerja dan Urgensi Pembentukan Badan Pusat Legislasi Nasional - Mario Agritama S W Madjid; Muhammad RM Fayasy Failaq; Vina Rohmatul Ummah; Ade Yulfianto (Universitas Islam Indonesia, 2023)
Regulatory dynamics in Indonesia are facing over-regulation or over-lapping caused by irregularities in the legislative institutions organization and harmonization of regulations. This is also inseparable from the sectoral ego of each institution. The presence of the Job Creation Law through the omnibus law method is considered a solution to overcome the problem of national regulations, but the existence of this law presents a new problem, namely the increasing number of derivative regulations that must be issued. This research focuses on two main issues: first, the legal and political capability of harmonizing regulations under the law through the Job Creation Law. Second, the urgency of establishing a National Legislation Center to overcome over-regulated and over-lapping regulations under the law This study uses a normative juridical type with literature studies. Data obtained from primary and secondary sources and analyzed qualitatively. The results of this study indicate that the legal politics of harmonization of the Job Creation Law does not have the capability to overcome the problems of laws and regulations under overlapping laws. Next, it is necessary to establish the Central National Legislative Body as a state institution under the President at the Ministry level with the function of controlling statutory regulations under the law so that they are not over-regulated or over-lapping.Keywords: Central Agency for National Legislation, Job Creation Law, Politics of Law AbstrakDinamika regulasi di Indonesia menghadapi situasi over-regulated atau over-lapping yang disebabkan oleh ketidakteraturan lembaga legislasi dalam menata dan mengharmonisasikan regulasi. Hal ini juga tidak terlepas dari ego sektoral masing-masing lembaga. Kehadiran Undang-Undang Cipta Kerja melalui metode omnibus law dianggap sebagai solusi untuk mengatasi persoalan regulasi nasional tersebut, akan tetapi keberadaan undang-undang tersebut menghadirkan persoalan baru, yakni makin banyaknya regulasi turunan yang harus diterbitkan. Penelitian ini menitikberatkan pada dua masalah utama. Pertama, kapabilitas politik hukum harmonisasi peraturan di bawah undang-undang melalui UU Cipta Kerja. Kedua, urgensi pembentukan Badan Pusat Legislasi Nasional untuk mengatasi over-regulated dan over-lapping peraturan di bawah undang-undang. Penelitian ini menggunakan metode yuridis normatif dengan studi kepustakaan. Data yang diperoleh dari sumber-sumber primer maupun sekunder dan ditelaah secara kualitatif. Hasil penelitian ini menunjukan bahwa politik hukum harmonisasi UU Cipta Kerja tidak memiliki kapabilitas untuk mengatasi problematika peraturan perundang-undangan di bawah undang-undang yang tumpang tindih. Berikutnya, perlu untuk dibentuk Badan Pusat Legislasi Nasional sebagai lembaga negara di bawah Presiden setingkat Kementerian dengan fungsi mengontrol peraturan perundang-undangan di bawah undang-undang agar tidak over-regulated maupun over-lapping.Kata Kunci: Badan Pusat Legislasi Nasional, Politik Hukum, UU Cipta Kerja